Reliving the Second Chimurenga: a nationalist female perspective - Gwarinda, Muchineripi (UNISA Press, 2021)
The aim of this article is to add a non-black, non-white female dimension to the male dominated discourse of the Chimurenga. The collective hero in female narratives is compared and contrasted to the individual hero in male narratives. A narration by a non-white, non-black female nationalist challenges the black-white binary perception of the struggle, heroism and legitimacy in black and white narratives.